2019
DOI: 10.1002/aelm.201800991
|View full text |Cite
|
Sign up to set email alerts
|

Printable High‐Aspect Ratio and High‐Resolution Cu Grid Flexible Transparent Conductive Film with Figure of Merit over 80 000

Abstract: Figure of merit (FOM), the ratio of electrical conductance to optical transparency, is an important metric to evaluate transparent conductive film (TCF). The conductivity of commonly used flexible TCF such as indium tin oxide is generally limited and their FOM is lower than 300. In this study, a high‐performance copper (Cu) metal‐mesh TCF with the highest FOM ever reported, up to 8 × 104, is fabricated through an additive manufacturing process of blading a silver seed layer and selective electroplating of Cu. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 39 publications
0
73
0
Order By: Relevance
“…Chen et al reported recently a copper grid TH with an outstanding Haacke's FoM over 7820.10 −3 Ω sq −1 (see Figure 1c), and a fast heating rate at low voltage. [ 56 ] This clearly illustrates the efficiency of such technology as TH.…”
Section: Principle Of Thsmentioning
confidence: 80%
See 4 more Smart Citations
“…Chen et al reported recently a copper grid TH with an outstanding Haacke's FoM over 7820.10 −3 Ω sq −1 (see Figure 1c), and a fast heating rate at low voltage. [ 56 ] This clearly illustrates the efficiency of such technology as TH.…”
Section: Principle Of Thsmentioning
confidence: 80%
“…The arrows below represent roughly the typical maximum steady‐state temperatures for the main TH technologies. c) Optical transparency versus sheet resistance diagram for different TH technologies based on transparent conductive oxides (TCO), [ 14,33,58–60 ] carbon nanotubes (CNT), [ 27,33,61 ] graphene, [ 57,62,63 ] metallic nanowire (MNW) networks, [ 64–70 ] metallic grids‐meshes, [ 56,71–76 ] conductive polymers, [ 49,50,77,78 ] and nanocomposites. [ 22,48,51,79–81 ] The dashed lines correspond to different values of Haacke's FoM: 10 000, 1000, 100, 10, 1 times 10 −3 Ω sq −1 .…”
Section: Principle Of Thsmentioning
confidence: 99%
See 3 more Smart Citations